2017
DOI: 10.17524/repec.v11i0.1724
|View full text |Cite
|
Sign up to set email alerts
|

Agressividade Tributária: Um Survey da Literatura

Abstract: Objetivo e Método: o objetivo deste artigo é revisar os estudos internacionais e no Brasil sobre a agressividade tributária, esta entendida como o comportamento de tentar evitar ou minimizar o ônus tributário explícito para a corporação. Enquanto tema de pesquisa acadêmica, o tax aggressiveness ou tax avoidance revela-se em um tópico diversificado e vasto, embora relativamente recente. Resultados e Contribuições: Entre as perguntas de pesquisa que nessa temática se desenvolvem, destaquem-se a identificação de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
50

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(127 citation statements)
references
References 109 publications
0
47
0
50
Order By: Relevance
“…Comprovada a natureza dessa relação, verificou se a governança corporativa interfere nessa associação. A temática da agressividade fiscal tem despertado crescente interesse resultado de uma combinação recente de fatores políticos, econômicos e tecnológicos (Martinez, 2017).…”
Section: Conclusãounclassified
“…Comprovada a natureza dessa relação, verificou se a governança corporativa interfere nessa associação. A temática da agressividade fiscal tem despertado crescente interesse resultado de uma combinação recente de fatores políticos, econômicos e tecnológicos (Martinez, 2017).…”
Section: Conclusãounclassified
“…The importance of DTT results largely in the reduction of dividend withholding tax rates (also the reduction of tax rates of interests and payments regarding intellectual property, among others). Martinez [17] identified the potential determinants of tax aggressiveness in firms, appreciating characteristics of the firms, environmental attributes, gatekeepers' restrictions, and company incentives. Abdixhiku et al [18] found a positive relationship between tax evasion and the tax rate and identified minor effects on the macroeconomic environment (focused on transition economies).…”
Section: Literature Review and Theoretical Considerationsmentioning
confidence: 99%
“…Thus, it is inevitable that there is doubt as to whether certain practices can be adopted to diminish, remove or delay the incidence of taxes. Companies take such risks to increase their own revenues, but are confronted by the reality that there is pressure on the state to confront abusive tax behavior, and collecting more tax revenue (Martinez, 2017).…”
Section: Theoretical Referencesmentioning
confidence: 99%